(untitled) (Bangladesh Pharmaceutical Journal, 2022)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has been a healthcare disaster because of the unique and distinct characteristics of the pathogen, the easy and rapid transmission of the virus from humans to humans, the challenges in diagnosis and confirmation of the disease and the inability to invent and distribute safe and effective drugs or vaccines worldwide that would work against all the variants of coronavirus. Bangladesh, despite being a third-world country with limited health resources, has not been one of the worst-hit countries in the world but has still suffered with the loss of nearly eleven thousand people. Traditional and herbal remedies have become popular in this sub-continent since long ago and used for the treatment and management of different diseases including infectious disease. In this review, we have summarized the reports of immunostimulating, anti-inflammatory, antiviral, and respiratory distress syndrome improving activities of prospective indigenous plants of Bangladesh that may be recommended for use as complementary and alternative medicine or may be potential sources for the discovery and development of anti-COVID-19 medicaments. Thus, the review will be beneficial for the researchers, complementary and alternative medicines or herbal medicine manufacturers, formulators to find out and manage the potential herbal/nutraceutical/medicinal agents for the preparation of complementary and alternative medicines, as well as to the scientist for further research for the discovery and development of therapeutics/new drugs for the prevention and treatment of COVID-19 as well as other viral infections. Bangladesh Pharmaceutical Journal 25(1): 89-114, 2022 (January)